Parkinson’s disease and mitochondrial complex I: a perspective on the Ndi1 therapy - Marella, Mathieu (2009)
Mitochondrial impairment has been collecting more and more attention as a contributing factor to the etiology of Parkinson’s disease. Above all, the NADH-quinone oxidoreductase, complex I, of the respiratory chain seems to be most culpable. Complex I dysfunction is translated to an increased production of reactive oxygen species and a decreased energy supply. In the brain, the dopaminergic neurons are one of the most susceptible cells. Their death is directly linked to the disease apparition. Developing an effective gene therapy is challenged by harmful actions of reactive oxygen species. To overcome this problem a therapeutic candidate must be able to restore the NADH-quinone oxidoreductase activity regardless of how complex I is impaired. Here we discuss the potency of the yeast alternative NADH dehydrogenase, the Ndi1 protein, to reinstate the mitochondrial respiratory chain compensating for disabled complex I and the benefit Ndi1 brings toward retardation of Parkinson’s disease.